A Synthesis of Alstonlarsine A via Alstolucines B and F Demonstrates the Chemical Feasibility of a Proposed Biogenesis. Issue 4 (15th December 2022) - Barnes, Griffin L.; Hong, Allen Y.; Vanderwal, Christopher D.
Abstract: We offer a new biogenetic proposal for the origin of the complex alkaloid alstonlarsine A, through rearrangement of the Strychnos alkaloids alstolucines B and F. Further, we provide evidence of the chemical feasibility of this proposal in the facile conversion of synthetic alstolucines into alstonlarsine A through a short, efficient sequence of N ‐methylation, β‐elimination, and a cascade 1, 7‐hydride shift/Mannich cyclization. We believe that this is the first biogenetic proposal involving the " tert ‐amino effect", a hydride‐shift‐based internal redox trigger of a Mannich cyclization. A further interesting feature of the cascade is that its stereochemical outcome most likely originates in conformational preferences during the hydride shift. Abstract : Alstonlarsine A, an indole monoterpene alkaloid isolated from Alstonia plants, was prepared by a rearrangement of other Alstonia alkaloids, alstolucines B and F. The successful process was patterned after a revised biogenetic proposal that features the first example of the "tert ‐amino effect" in alkaloid biogenesis.